Histological Effects of Inhaled Corticosteroids and ss(2)-agonists on Laryngeal Mucosa in an Allergic Rat Model - ERCAN, FERİHA (SAGE PUBLICATIONS LTD, 2013)
Objective To constitute an animal model of laryngeal allergy and evaluate the laryngeal effects of inhaled corticosteroids and ss(2)-agonists on the laryngeal mucosa in an allergic rat model. Study Design Prospective randomized. Setting The Experimental Medical Research Institute (DETAE) at Istanbul University. Subjects and Methods Wistar Albino rats (n = 32) were sensitized with ovalbumin. Unsensitized rats (n = 8) served as controls. The rats were exposed to aerosolized ovalbumin (1%). On days 28 through 42, every 2 days preceeding ovalbumin exposure, rats were further exposed to aerosolized phosphate buffered saline (n = 8), fluticasone propionate (n = 8), salbutamol (n = 8), and combined salbutamol+fluticasone propionate (n = 8). Inflammatory cell infiltration was graded semi-quantitatively. The quantitative data included mast cell count and degranulation. Ultrathin sections were investigated under transmission electron microscope. Results The simultaneous and pairwise comparison of groups (Kruskal-Wallis) revealed statistically significant difference among groups at supraglottic level (critical P < .05, <.01) and no difference at glottic level. In ovalbumin+phosphate buffered saline exposed rats, the light microscopy of supraglottic mucosa revealed regular epithelium with severe inflammatory cell infiltration and increased mast cell count. Electron microscopy revealed increased mast cell degranulation. Increased inflammatory cell infiltration was detected along with reduced mast cell count among fluticasone propionate treated rats. Mild inflammatory cell infiltration was encountered in combined salbutamol+fluticasone propionate treated rats. Conclusion This study supported the presence of localized allergic reaction in the supraglottic laryngeal mucosa through the observation of increased mast cell number and degranulation. It was also shown that inhaled corticosteroids increase inflammation whereas combined inhaled corticosteroids and ss(2)-agonists minimize allergic and inflammatory reactions in supraglottic laryngeal mucosa providing a safer therapeutic option.
Keywords: laryngeal mucosa; laryngeal allergy; inhaled corticosteroids; ss(2)-agonists; mast cells; degranulation; inflammation; MAST-CELLS; FLUTICASONE; SALMETEROL; INFLAMMATION; CHALLENGE; ASTHMA; EDEMA